A rare case of primary congenital glaucoma in combination with neurofibromatosis 1: a case report. Issue 1 (December 2015) - Li, Haijun; Liu, Ting; Chen, Xia; Xie, Lin
Abstract Background Neurofibromatosis 1 (NF1) is a common disease that mainly affects the skin and peripheral nervous system, and is characterized by bony dysplasia. Primary congenital glaucoma (PCG) is a sight-threatening disease that can manifest as a prodrome of NF1, especially in newborn babies. We report a case of PCG with NF 1. Case presentation A 1-month-old boy presented with an enlarged right eyeball. An increased IOP and typical glaucomatous optic neuropathy were found, on the initial physical examination, a clinical diagnosis of primary congenital glaucoma (PCG) was made and a trabeculectomy with mitomycin C (MMC) therapy was subsequently performed. Three year later, the boy again presented with an even larger right eye and a gradually expanding left one. In addition to typical glaucomatous optic neuropathy, the boy also had multiple café au lait patches all over his body, megacephaly (head circumference = 60 cm; body weight = 14 kg; height = 93 cm) and remarkable facial features included swollen, soft upper eyelids and a flat, broad nose sphenoid wing dysplasia, eyelid thickening, bony orbit enlargement were found. Conclusions It is rare have both PCG and NF1, and PCG may be a prelude to NF1. Continuous follow-up should be advised and we should raise our awareness of the combined condition and to improve chances for an early diagnosis.